Integrating Tharu Indigenous Culture in English Language Teaching: An Action Research - Dahal, Dadhiram (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
The effect of integrating local (indigenous) culture into the course of English language teaching has not been explored much in Nepal. This study aims to investigate the Tharu indigenous festival ‘Joorshital’ in its socio-cultural aspects and integrates the festival into an English language course by designing activities relating to teaching and learning English inside and outside the classroom. This study used qualitative method to collect and analyze the data. The study took 30 students of Grade 5 from a secondary school in Itahari, Sunsari as the subjects for the study. The surveys among the students and parents before and after the implementation of the action research, students’ and parents’ written comments, and student observation were employed to record the changes in motivation and enthusiasm for learning English during a one-year study period. The data resources included the Tharu community, Tharu students, Tharu social leaders and elderly people, students’ prior knowledge of ‘Joorshital’, online resources, and journal articles. The data were collected through field visits, questionnaires, interviews, and observation. The students were very enthusiastic and active in cross-cultural activities. They became more motivated, interactive, and participatory in learning English when the indigenous cultural contents were integrated into the course. Their level of interest increased; and they enjoyed the process thoroughly. Such studies are very beneficial to the teachers to promote cross-cultural awareness among themselves and the students, to help the indigenous culture to preserve, and to motivate them in English learning through interactive engagements.